2017
DOI: 10.3390/rs9050445
|View full text |Cite
|
Sign up to set email alerts
|

Better Estimated IEM Input Parameters Using Random Fractal Geometry Applied on Multi-Frequency SAR Data

Abstract: Abstract:Microwave remote sensing can measure surface geometry. Via the processing of the Synthetic Aperture Radar (SAR) data, the earth surface geometric parameters can be provided for geoscientific studies, especially in geological mapping. For this purpose, it is necessary to model the surface roughness against microwave signal backscattering. Of the available models, the Integral Equation Model (IEM) for co-polarized data has been the most frequently used model. Therefore, by the processing of the SAR data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…This is in accordance with several previous studies which have found that, for agricultural surfaces, the exponential function provides the best match between predicted and SAR backscatters [82][83][84][85]. Generally speaking, in spite of the slight underestimation, one can state that the simulations of IEM by using the measured L are very satisfying with respect to what have been reported in previous works [20,67,80,81,86]. However, measuring the correlation length is a problematic task because of its dependence on the profile length, as well as the standard deviation of surface height (Hrms) [86], and thus its is considered as the most difficult parameter to be measured at the field with a good accuracy.…”
Section: Evaluation Of the Oh And Iem Modelssupporting
confidence: 92%
See 1 more Smart Citation
“…This is in accordance with several previous studies which have found that, for agricultural surfaces, the exponential function provides the best match between predicted and SAR backscatters [82][83][84][85]. Generally speaking, in spite of the slight underestimation, one can state that the simulations of IEM by using the measured L are very satisfying with respect to what have been reported in previous works [20,67,80,81,86]. However, measuring the correlation length is a problematic task because of its dependence on the profile length, as well as the standard deviation of surface height (Hrms) [86], and thus its is considered as the most difficult parameter to be measured at the field with a good accuracy.…”
Section: Evaluation Of the Oh And Iem Modelssupporting
confidence: 92%
“…Generally speaking, in spite of the slight underestimation, one can state that the simulations of IEM by using the measured L are very satisfying with respect to what have been reported in previous works [20,67,80,81,86]. However, measuring the correlation length is a problematic task because of its dependence on the profile length, as well as the standard deviation of surface height (Hrms) [86], and thus its is considered as the most difficult parameter to be measured at the field with a good accuracy. In the same vein, several studies have reported that the discrepancies between backscattering coefficients simulated by IEM and those measured by SAR sensors are mainly related to the value of L measured [87,88].…”
Section: Evaluation Of the Oh And Iem Modelssupporting
confidence: 81%
“…The I 2 EM is applicable on a wide range of surfaces, from smooth to rough where k 0 s < 3 for a certain radar wavenumber. The co-polarized backscattering coefficient equation according to [4,10,11]:…”
Section: Improved Integral Equation Model (I 2 Em)mentioning
confidence: 99%
“…and pp is either the hh or vv polarizations, and W (n) is the Fourier transform of nth power of the autocorrelation function (ACF) of the rough surface [10]. f hh , f vv , F hh , and F vv are approximated by the following equations:…”
Section: Improved Integral Equation Model (I 2 Em)mentioning
confidence: 99%
“…Feature detection from SAR images is another major topic in Microwave Remote Sensing. Ghafouri et al [17] present a method to better estimate IEM (Integral Equation Model) input parameters for multi-frequency SAR data. Di Martino et al [18] describe the role of resolution for the estimation of fractal dimension maps.…”
mentioning
confidence: 99%